Local anesthetic lidocaine-encapsulated polymyxin-chitosan nanoparticles delivery for wound healing: in vitro and in vivo tissue regeneration - Yanyan Qi; Xiangyan Yao; Xianhui Du; Songtao An (Taylor & Francis Group, 2021)
In relieving local pains, lidocaine, one of ester-type local anesthetics, has been used. To develop the lidocaine membranes of enhanced local anesthetic effects, we have designed to establish the composition of wound dressings based on lidocaine chloride (LCH) (anesthetic drug)-loaded chitosan (CS)/polymyxin B sulfate (PMB). The LCH membranes (LCH-CS/PMB) was fabricated by the LCH oxide solutions within the CS/PMB matrix. The influences of different experimental limitations on CS/PMB membrane formations were examined. The double membrane particle sizes were evaluated by scanning electron microscopy (HR-SEM). Additionally, antibacterial efficacy was developed for gram-positive and negative microorganisms. Moreover, we examined in vivo healing of skin wounds formed in mouse models over 16 days. In contrast to the untreated wounds, rapid healing was perceived in the LCH-CS/PMB-treated wound with less damaging. These findings indicate that LCH-CS/PMB-based bandaging materials could be a potential innovative biomaterial for tissue repair and regeneration for wound healing applications in an animal model.